Refraining from culture-related discussions in English as a foreign language classrooms: lessons from negative cases - Lavrenteva, Evgenia; Orland-Barak, Lily (Frontiers in Education, 2024)
Introduction This study examined the factors that determined English as a Foreign Language (EFL) teacher decisions to refrain extending the use of culture-related classroom discussions. Specifically, we focused on the episodes in which teachers decided against holding specific culture-related discussions, to better understand the reasons for limited inclusion of diverse cultural content. Methods In our examination of the data, we opted for the Theory of Planned Behavior as a lens to interpret teachers' motives for deciding at will not to have a culture-related discussion. The study followed negative case methodology to gain insight into why teachers avoided classroom discussions about culture. Within this methodology, we applied the Possibility Principle to define and select relevant sample of cases. To analyse the cases, we employed hybrid approach of qualitative methods of thematic analysis. Results A thematic analysis of teacher interviews (N = 30) revealed that Israeli EFL teachers' decisions to refrain from culture-related classroom discussions were influenced by their personal norms and attitudes, perceptions of their roles as teachers, social conventions, and expectations of various school stakeholders. Specifically, we found that the major barriers to conducting culturally-related classroom conversations in the Arab sector had to do with the values endorsed by the school culture, with teachers' tendency to avoid taboo topics in their teaching due to concerns about how students would react or become alienated. For immigrant teachers, personal norms and perceptions of control operated as key factors in their decisions to avoid sensitive issues. Majority teachers cited negative attitudes, moral panics, school culture and perceptions of control as principal reasons for avoiding controversial topics. Discussion The emergent patterns are discussed as embedded in the cultural and social norms with possible implications for teaching in the multicultural classroom.